Growth of c‐plane and m‐plane aluminium‐doped zinc oxide thin films: epitaxy on flexible substrates with cubic‐structure seeds. Issue 2 (19th March 2020) - Li, Yongkuan; Liu, Xinxing; Wen, Dan; Lv, Kai; Zhou, Gang; Zhao, Yue; Xu, Congkang; Wang, Jiangyong
Abstract : Epitaxial growth of c ‐plane and m ‐plane hexagonal‐structure aluminium‐doped zinc oxide thin films is achieved for the first time on flexible substrates using cubic‐structure seeds. This technique offers transparent electrodes and epitaxy seeds for orientation‐controllable ZnO (and GaN) devices. Abstract : Manufacturing high‐quality zinc oxide (ZnO) devices demands control of the orientation of ZnO materials due to the spontaneous and piezoelectric polarity perpendicular to the c ‐plane. However, flexible electronic and optoelectronic devices are mostly built on polymers or glass substrates which lack suitable epitaxy seeds for the orientation control. Applying cubic‐structure seeds, it was possible to fabricate polar c ‐plane and nonpolar m ‐plane aluminium‐doped zinc oxide (AZO) films epitaxially on flexible Hastelloy substrates through minimizing the lattice mismatch. The growth is predicted of c ‐plane and m ‐plane AZO on cubic buffers with lattice parameters of 3.94–4.63 Å and 5.20–5.60 Å, respectively. The ∼80 nm‐thick m ‐plane AZO film has a resistivity of ∼11.43 ± 0.01 × 10 −4 Ω cm, while the c ‐plane AZO film shows a resistivity of ∼2.68 ± 0.02 × 10 −4 Ω cm comparable to commercial indium tin oxide films. An abnormally higher carrier concentration in the c ‐plane than in the m ‐plane AZO film results from the electrical polarity along the c ‐axis. The resistivity of the c ‐plane AZO film drops to the order of 10 −5 Ω cm at 500 K owing to the semiconducting behaviour. Epitaxial AZO films with low resistivities and controllable orientations on flexible substrates offer optimal transparent electrodes and epitaxy seeds for high‐performance flexible ZnO devices.